Cyprus : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cyprus. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that the Cypriot economy has achieved an impressive turnaround since the 2012-13 banking crisis. GDP growth has been accelerating for three consecutive years on strong foreign demand. Rising labor demand has sharply lowered the unemployment rate to 10.3 percent as of September 2017. Emergency liquidity assistance to banks has been fully repaid. Gains in cost competitiveness and strong foreign demand have narrowed the underlying current account deficit (excluding large one-off imports). The current strong growth momentum is expected to persist for the next several years, underpinned by ongoing large construction projects and weak payment discipline.